2008
DOI: 10.1590/s0100-879x2008000800011
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of naive and memory T lymphocytes with sustained high cellular activation during the first year of life from uninfected children born to HIV-1-infected mothers on HAART

Abstract: The immune consequences of in utero HIV exposure to uninfected children whose mothers were submitted to highly active antiretroviral therapy (HAART) during gestation are not well defined. We evaluated 45 HIV-exposed uninfected (ENI) neonates and 45 healthy unexposed control (CT) neonates. All HIV-infected mothers received HAART during pregnancy, and the viral load at delivery was <50 copies/mL for 56.8%. Twenty-three ENI neonates were further evaluated after 12 months and compared to 23 unexposed healthy age-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 36 publications
(27 reference statements)
5
45
1
1
Order By: Relevance
“…We have shown that children born from female kidney recipents taking azathioprine, one calcineurin inhibitor and prednisone during gestation presented at birth a characteristic immune profile: 80% ( (27). A reduced expression of activation markers on CD8þT cells, an increased percentage of activated and exhausted memory B cells and low CD4þTreg percentages were also observed at birth.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We have shown that children born from female kidney recipents taking azathioprine, one calcineurin inhibitor and prednisone during gestation presented at birth a characteristic immune profile: 80% ( (27). A reduced expression of activation markers on CD8þT cells, an increased percentage of activated and exhausted memory B cells and low CD4þTreg percentages were also observed at birth.…”
Section: Discussionmentioning
confidence: 95%
“…At birth, 16 out of 20 (80%) children in the Transplant group had low numbers of B cells; low CD4þT cells were observed in 3/20 (15%), low CD8þ T cells, in 3/20 (15%) and low NK cells, in 5/20 children (25%) (27,28). Of note, all neonates who presented with low T or NK cell numbers had also low B cell numbers.…”
Section: Characteristics Of Mothers and Infantsmentioning
confidence: 96%
“…Normally, the immune system is functionally immature at birth and undergoes a sequential development that is reflected in changing leukocyte values, a process that is genetically determined and additionally stimulated by antigen exposure (28). In the context of pediatric HIV infection, the principal immunologic change documented in large, multicentric, and longitudinal studies has been the CD4 T-lymphocyte count, which decreases rapidly in infected infants and children if compared to HIV-exposed (but uninfected) control subjects (1,14,19,22). Documented evidence shows that reference values are given for the major lymphocyte subsets, including B cells, NK cells, and T cells, including both T-helper and cytotoxic T-cell subsets (8,10,17,20).…”
Section: /Cd8mentioning
confidence: 99%
“…Also, the antiretroviral (ARV) prophylaxis of vertical transmission can act on the placental environment, causing changes in cytokine expression (9). The newborns present abnormalities in mitochondrial function (2), in hematological features (5,10,17), and in the maturation of T and B lymphocytes (3,4,8,11,12,20,24,25).…”
mentioning
confidence: 99%